2008
DOI: 10.2310/7750.2008.07073
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Exposed Bones and Joints in Critically Ill Patients: Lower Extremity Salvage with Topical Negative Pressure Therapy

Abstract: The patients described in this study were severely compromised by systemic and vascular disorders, so extremity amputation had been considered owing to the overall condition and the exposure of tendons and bones. Since it was possible to salvage the affected limbs with this straightforward and simple procedure, this type of treatment should be considered as a last attempt to prevent amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
20
0
3
Order By: Relevance
“…observed in wounds treated with NPWT as opposed to conventional therapy. The rate of granulation tissue formation has been reported to be slower than would be expected for acute, non-ischaemic wounds at six to 14 days, it therefore may not be appropriate to assess the wound for progression towards healing any sooner than one week of therapy [66]. Dressing changes should however be carried out every two to three days as a minimum to ensure that there is no deterioration of the wound.…”
Section: Primary Goalmentioning
confidence: 94%
See 4 more Smart Citations
“…observed in wounds treated with NPWT as opposed to conventional therapy. The rate of granulation tissue formation has been reported to be slower than would be expected for acute, non-ischaemic wounds at six to 14 days, it therefore may not be appropriate to assess the wound for progression towards healing any sooner than one week of therapy [66]. Dressing changes should however be carried out every two to three days as a minimum to ensure that there is no deterioration of the wound.…”
Section: Primary Goalmentioning
confidence: 94%
“…Clare et al [43] (L3) reported that six of eight wounds with severe PVD healed completely following NPWT. Horch et al [66] (L3) reported a series of 21 patients with CLI all of whom successfully received a STSG following NPWT. Vuerstaek et al [68] (L1) reported a RCT of a mixed group of lower limb ulcers, over half of which had an arterial component to them (with ABI values as low as 0.6).…”
Section: Use Of Npwt In Wounds Of the Ischaemic Lower Limbmentioning
confidence: 98%
See 3 more Smart Citations